2013
DOI: 10.21432/t2w88v
|View full text |Cite
|
Sign up to set email alerts
|

Elementary students’ affective variables in a networked learning environment supported by a blog: a case study / Variables affectives des élèves du primaire dans un contexte d'apprentissage en réseau soutenu par un blogue: une étude de cas

Abstract: This study documents to what extent writing on a blog in a blended learning environment could influence the affective variables of elementary-school students’ writing. We grounded our framework more specifically in Deci and Ryan’s theory of self-determination. Our research team used both pre and post-tests and we conducted the analysis on the basis of inferential and correlational statistics using SPSS 17®. Results indicate an increase in motivation to write in pupils who used the blog, whereas the number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Such studies demonstrated these autonomous motives were positively related to upper-elementary grade students’ writing performance (De Smedt et al, 2016, 2018), and writing with a peer lowered controlled motives for writing (De Smedt et al, 2019, 2020). A study by Allaire et al (2013) found that intrinsic motivation was enhanced when students wrote a blog in a networked learning environment, but Harris et al (2006) indicated intrinsic motives for writing were not changed when second-grade students were taught strategies for planning and drafting text. Contrary to expectations, Limpo, Vigário, et al (2020) found intrinsic motives for writing were lowered as a result of handwriting instruction, and Guay et al (2010) reported primary grade students placed similar emphasis on intrinsic and autonomous motives for writing.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Such studies demonstrated these autonomous motives were positively related to upper-elementary grade students’ writing performance (De Smedt et al, 2016, 2018), and writing with a peer lowered controlled motives for writing (De Smedt et al, 2019, 2020). A study by Allaire et al (2013) found that intrinsic motivation was enhanced when students wrote a blog in a networked learning environment, but Harris et al (2006) indicated intrinsic motives for writing were not changed when second-grade students were taught strategies for planning and drafting text. Contrary to expectations, Limpo, Vigário, et al (2020) found intrinsic motives for writing were lowered as a result of handwriting instruction, and Guay et al (2010) reported primary grade students placed similar emphasis on intrinsic and autonomous motives for writing.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Keeping in mind that motivation is one of the engines that drives learning and that nowadays students have a broader mastery of new technologies compared to adults, ICTs can be quite stimulating and motivating and can be transformed into ideal instruments to respond to the new type of students. This was reflected in [24][25][26][27][28][29], where students showed higher levels of motivation and using new technologies was proven to deliver a more effective way of learning.…”
Section: Motivationmentioning
confidence: 99%
“…WebQuest, por sua vez, é uma tecnologia de investigação orientada utilizada no momento da produção textual para a criação de determinados blogs 22 . O blog, por sua vez, é um diário virtual de conteúdo diversificado em que adolescentes se encontram para expressar opiniões e ideias distintas 23 .…”
Section: Outras Opções Tecnológicas Podem Ser Adotadas Como é Caso Do...unclassified